Pronominated nominal forms in the Wolfenbüttel Postil (1573–1574)4) - Gelumbeckaitė, Jolanta (Baltistica, 2020)
The article deals with the pronominated word forms, which are intended to mark definiteness in the nominal domain, and with their usage in the Wolfenbüttel Postil (1573–1574). The function of the pronominated forms in Old Lithuanian is only vaguely defined. (Old) Lithuanian shows a more complex structure of reference differences than a mere morphological dichotomy pronominated (definite) vs. simple (indefinite, non-definite). It is therefore relevant to evaluate the entire data of a closed text corpus which represents neither a purely canonical translation nor a continuously translated text. The Wolfenbüttel Postil (over 131,000 text words) is suitable for the investigation of pronominated nominal forms in Old Lithuanian, since it represents a mixture of an originally written and a translated text, the latter being a translation of canonical and non-canonical text.